Peran Manajemen Sumber Daya Manusia dalam Organisasi : Studi Kasus PT Telkom Indonesia - Arief Rachman Afandy; Zainul Abidin; Zainul Qudsi; Samsul Arifin; Syafiul Anam (Jurnal Manajemen Bisnis Digital Terkini, 2025)
Human resource management (HRDM) is a crucial factor in supporting the success of companies in the digital era which is full of rapid change and global competition. Companies are required to not only adapt to technology, but also be able to build strategic and innovation-oriented MSDM systems. This study aims to examine the strategic role of MSDM in PT Telkom Indonesia (Persero) Tbk in supporting digital transformation and achieving organizational goals. Using a literature study approach, data was obtained from books, scientific journals, company annual reports, and official online sources. The results of the study show that PT Telkom Indonesia manages human resources strategically through various initiatives, such as the Great People Development Program (GPDP), digitization of the Human Capital Management (HCM) system, and strengthening the value-based work culture of "The Telkom Way" which includes Integrity, Enthusiasm, and Totality. This approach has a positive impact on increasing employee engagement, productivity, innovation, and the company's competitiveness in the highly competitive telecommunications industry. In addition, the implementation of digital technologies in HR management, such as the use of analytics platforms for performance measurement and online learning systems, has helped companies in accelerating the internal transformation process. However, challenges such as the digital divide between employees, differences in expectations between generations, and resistance to change are still obstacles that need to be addressed with a more inclusive, adaptive, and employee-well-being-oriented management strategy. This research provides the implication that the integration of technology, organizational culture, and talent development is an important combination in creating a resilient and sustainable HR system. The limitations of the research lie in the literature approach that has not touched the empirical aspect, so it is recommended that there be field studies or in-depth interviews with related parties in the next research to get a more holistic and accurate picture.